(3GdJMa GdYXGe hGdCMGOjK GdcQGe aj aVGFd GdTGes - (3Ydj Hf eMeO Hf UGaj Hf TLGY GdQHYj, CHh GdMSf, hjYQa HGHf CHj Gdghd,J (B444 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG cJGH ai aVGFd OeTb hGdTGe eeG LeY Pdc GdQHYi hCPcQg eMPha GdCSGfjO s
(3gh eNJUQ (B" (3aVGFd GdTGe (B" (3HBNQgG eDQN SfI (B940(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B95 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI HjQhJ ef GdQTJ s
Keywords: (3GdJGQjNs